Improvement of methodical tools of the seasonal transportation irregularity assessment - D. A. Macheret; A. Yu. Ledney (Вестник Научно-исследовательского института железнодорожного транспорта, 2020)
Seasonal irregularity of transportation is one of the important production and economic issues for the transportation industry. This issue negatively affects operation of the railway transport as higher irregularity of transportation means limitation of the overall volume that can be realized within a year, which results in reduction of effectiveness of the industry resources use.When assessing the seasonal irregularity of transportation by means of the method, significant error takes place due to different number of days in the months. As one of the solutions of the problem, the authors propose the improved methodical tools for assessment of the seasonal irregularity of freight transportation. First, the average daily values of the relevant volumetric indicator are used rather than the general ones; second, the load on infrastructure is determined by both the quantity of transported tons and the distance of transportation. Therefore the seasonal irregularity is determined by the loading, as well as by the freight turnover.Improved tools of assessment of the seasonal irregularity of freight transportation presented in the article allow significantly increasing its accuracy, which will promote quality improvement of planning and analysis of the railways operation and development.